Educational prospects in physical education, recreation, sports and physical activity (Impetus, 2021)
The prospects of teaching-learning in Education, physics, recreation, Sport and physical activity, is to rethink the teaching strategies, the way of transmitting the competences, consequently the thought is directed to try and study the essence of education trying to discover its cause in nature, can be assimilated as a constant approach through the development of discernment to the very way in which everything is created, no other being so far known has come so close to the properties of things, For this reason, it is a responsibility to have knowledge of the causes, think for example about meaningful motivational training, educate yourself in your own way, for your own subsistence and create, aided by factors such as the sciences of human motor skills, which coincide in the corporeality for the attribute of biopsychosocial motor development, it serves to partly dimension what it implies to deepen on the condition Of education, by its generality implies something that transcends the human being as a species, but that involves him with privileges such as reason, intelligence, will, etc., all faculties that allow him to understand it as no other organism can
Keywords: prospective; physical education; recreation; sport; physical activity; pedagogy